Unraveling chain specific ubiquitination in cells using tandem ubiquitin binding entities - Muhammad Shahzad Ali; Christopher Rainville; Janelle Pedroza; David E. Sterner; Hehe Wang; Kumar Suresh; Tauseef R. Butt (Scientific Reports)
Abstract Polyubiquitination of proteins serves distinct functions that are governed by the nature of polyubiquitin chains built on target proteins. Among the eight distinct type of ubiquitin chains, lysine 48 (K48)-linked chains are specifically associated with proteasomal degradation, while lysine 63 (K63)-linked chains are primarily involved in regulating signal transduction and protein trafficking. The ubiquitin-proteasome system (UPS) has recently been exploited in drug discovery and introduced PROTACs (Proteolysis Targeting Chimeras), or molecular glues (MGs), to hijack ubiquitin E3 ligases, to facilitate the targeted degradation of specific proteins. However, assessment of PROTAC or MG mediated endogenous target protein ubiquitination in a linkage-specific manner in high throughput format remains a challenge. In this study, we applied chain-specific TUBEs (Tandem Ubiquitin Binding Entities) with nanomolar affinities for polyubiquitin chains in HTS assays to investigate the ubiquitination dynamics of RIPK2, a key regulator of inflammatory signaling. Using L18-MDP to induce K63 ubiquitination of RIPK2 and RIPK degrader-2, a RIPK2 PROTAC to induce K48 ubiquitination, we demonstrate that chain-selective TUBEs can differentiate and unravel context dependent linkage specific ubiquitination of endogenous RIPK2. Potential application of this technology to other target proteins and cellular contexts will be discussed.